Self-similar rupture of thin free films of power-law fluids - Thete, Sumeet Suresh; Anthony, Christopher; Basaran, Osman A.; Doshi, Pankaj (Physical Review E, 2015)
The rupture of a thin free film of a power-law fluid under the competing influences of destabilizing van der Waals pressure and stabilizing surface tension pressure is analyzed. In such a fluid, viscosity decreases with the deformation rate raised to the n - 1 power where 0 < n <= 1 (n = 1 for a Newtonian fluid). When 6/7 < n <= 1, film rupture occurs under a balance between van der Waals pressure, inertial stress, and viscous stress. When n < 6/7, however, the dominant balance changes: Viscous stress becomes negligible and the film ruptures under the competition between van der Waals pressure, inertial stress, and surface tension pressure.